Laserová lécba diabetické retinopatie tĕhotných - Stibor, V; Strupplová, J; Kondrová, J; Traurigová, I (Ceskoslovenska oftalmologie, 1989)
During the regular follow-up of risk pregnancies in the Central Bohemian region, concentrated at the First Obstetric Clinic in Prague, the authors detected 34 women with retinopathies. In nine they performed panretinal photocoagulation by means of an argon laser and recorded favourable results. The authors consider early laser therapy of retinopathies in pregnant diabetics useful and essential. Advanced forms of diabetic retinopathy in pregnant women still remain a contraindication of pregnancy. Pregnancy in diabetic women is always a risk and it would be a mistake not to take this fact into account.
Keywords: těhotenství při diabetu; Female; Light Coagulation; fotokoagulace; Humans; ženské pohlaví; Pregnancy; diabetická retinopatie; lidé; Pregnancy in Diabetics; těhotenství; Diabetic Retinopathy